Smart theft alarm with image - Ab Ghani, Mohammad Azuan; Zakaria, Normah; Hamzah, Norhasyimah; Rubani, Siti Nur Kamariah (Penerbit UTHM, 2021)
The safety aspect is important in public life does not matter in the city or in rural areas. Results from the study found the first half of the year 2016 of 6,662 cases of house intrusion reported by Bernama. The objective of this study was to design, developing and testing and functional smart theft alarm with image to improve levels of safety at house. To ensure the success of this project, researchers adopted the model of the development of the prototype as the methodology of the project. Researchers using the raspberry Pi as unit controller to control this system. Telegram application was used on smart phone to able this system sent image using internet. Three experts have considered the prototype of this product. As a result of the development of the prototype of this product, the researchers found that the system can notify and sent image to house owner through the Telegram application. Application on the Smartphone makes users use and operate the prototype smart theft alarm.